Sosialisasi Perubahan Peran Orang Tua Pada Masa Pandemi Covid-19 Sebagai Bentuk Dukungan Pelaksanaan Learning From Home - Eny Kusumawati (Universitas Majalengka, 2021)
Every parent needs to have an understanding of the implementation of learning from home as a result of the Covid-19 pandemic, where there has been a change in the role that was originally carried out in the education unit has now changed in the family unit. This socialization activity aims to provide knowledge and understanding to parents of the importance of the role of parents during the Covid-19 pandemic as a form of support for the implementation of learning from home. This service activity was carried out in Dusun Kembang, Margosari, Pengasih with as many as 30 participants selected based on the presence or absence of school-age children in their household. This service activity is designed in three stages: (1) the planning stage begins with the need assessment, (2) the activity or implementation stage, (3) the activity evaluation stage. From the results of the evaluation, it can be concluded that (1) the socialization of changes in the role of parents during the Covid-19 pandemic as a form of support for the implementation of learning from home is very beneficial for parents, (2) parents have an understanding of the importance of the role of parents in accompanying children to learn at home.